2018
DOI: 10.1177/0961203317751061
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure control over time in childhood-onset systemic lupus erythematous

Abstract: Introduction Hypertension (HTN) is prevalent in patients with systemic lupus erythematosus (SLE) and causes early cardiovascular aging and progression of renal and cardiac disease. The aim of this longitudinal retrospective study was to evaluate the prevalence of HTN, the follow-up blood pressure trends, and risk factors for HTN in a population-based cohort with childhood-onset SLE (cSLE). Methods Demographic and clinical data of consecutive visits from the baseline to the last visit were extracted from electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The renal injury per se that is caused by nephritis is likely not the cause of the hypertension. This is supported by studies showing that hypertension is prevalent in child-onset SLE independent of the presence of nephritis [91]. In addition, Shaharir et al found that 53% of SLE patients were hypertensive without evidence of nephritis [20].…”
Section: Introductionmentioning
confidence: 76%
“…The renal injury per se that is caused by nephritis is likely not the cause of the hypertension. This is supported by studies showing that hypertension is prevalent in child-onset SLE independent of the presence of nephritis [91]. In addition, Shaharir et al found that 53% of SLE patients were hypertensive without evidence of nephritis [20].…”
Section: Introductionmentioning
confidence: 76%
“…A recent study reported arterial hypertension in approximately one-third of cSLE patients, almost 3 years after the disease onset. In multivariate analysis, lupus nephritis, obesity, and high frequency of extra-renal disease activity were independent predictors of arterial hypertension at baseline [ 123 ]. Prompt adjuvant treatment of arterial hypertension and proteinuria should be recommended for all cSLE patients [ 96 ].…”
Section: Management Data and Drugs For Cslementioning
confidence: 99%
“…Controlled blood pressure was defined as individuals both on ≥1 antihypertensive medication and with blood pressure less than the 90th percentile referenced to sex, height, and age. 25,26 Uncontrolled blood pressure was defined as individuals on ≥1 medications with readings greater than the 90th percentile referenced to sex, height, and age. Antihypertensive medications were categorized as angiotensin-converting enzyme inhibitors, calcium channel blockers, or other, which included β-blockers, α-blockers, angiotensin receptor blockers, diuretics, and vasodilators.…”
Section: Methodsmentioning
confidence: 99%
“…Controlled blood pressure was defined as individuals both on ≥1 antihypertensive medication and with blood pressure less than the 90th percentile referenced to sex, height, and age. 25,26 Uncontrolled blood pressure was defined as individuals on ≥1 medications with readings greater than the 90th percentile referenced to sex, height, and age.…”
Section: Blood Pressure and Medicationsmentioning
confidence: 99%